Estimation of spicule magnetic field using observed kink waves - Singh K.A.P.; Dwivedi B.N. (My University, 2025)
We apply the method of MHD seismology to estimate the magnetic field in spicules using observed kink waves. We include the effects of gravitational stratification, the neglect of which leads to an error of around 30% in the estimation of the magnetic field. With stratification included, we find the magnetic field in spicules in the range of 8-16 G. We also estimate a density of 7.4 × 10-10 kg m-3 in spicules. The estimated values of magnetic field and density are in agreement with the available observations. Improved measurement of height, oscillation period, and plasma density in spicules will further enhance the precision of this method. © 2007 Elsevier B.V. All rights reserved.